2014
DOI: 10.1016/j.biopsycho.2014.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Neural substrates of rumination tendency in non-depressed individuals

Abstract: a b s t r a c tThe tendency to ruminate, experienced by both healthy individuals and depressed patients, can be quantified by the Ruminative Response Scale (RRS). We hypothesized that brain activity associated with rumination tendency might not only occur at rest but also persist to some degree during a cognitive task. We correlated RRS with whole-brain fMRI data of 20 healthy subjects during rest and during a face categorization task with different levels of cognitive demands (easy or difficult conditions). O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 69 publications
4
28
1
Order By: Relevance
“…Despite evidence implicating all three networks in rumination in adults (Berman et al , 2011, 2014; Hamilton et al , 2011; Kuhn et al , 2012, 2014; Piguet et al , 2014; Luo et al , 2015), we found that coherence of SN, but not of DMN or ECN, was associated with brooding. The SN, which includes the anterior insula, dACC, and frontopolar regions, receives afferent inputs from subcortical and limbic structures involved in emotion processing and in motivation (Menon, 2011), as well as autonomic inputs (Craig, 2002).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Despite evidence implicating all three networks in rumination in adults (Berman et al , 2011, 2014; Hamilton et al , 2011; Kuhn et al , 2012, 2014; Piguet et al , 2014; Luo et al , 2015), we found that coherence of SN, but not of DMN or ECN, was associated with brooding. The SN, which includes the anterior insula, dACC, and frontopolar regions, receives afferent inputs from subcortical and limbic structures involved in emotion processing and in motivation (Menon, 2011), as well as autonomic inputs (Craig, 2002).…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, high-ruminating adults exhibit stronger SN-ECN connectivity (Kuhn et al , 2012) than do their low-ruminating peers. Thus, it is possible that in girls who exhibit higher levels of brooding, when the SN, which is already strongly coherent, integrates with the DMN and ECN, the DMN and ECN may not be equipped for the strength and potentiation of the SN activation, which may explain the over-coherence within DMN and under-coherence within ECN that has been found to be associated with ruminative brooding in adults (Berman et al , 2011; Hamilton et al , 2011, 2014; Kuhn et al , 2012; Piguet et al , 2014; Luo et al , 2015). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, individuals with anxiety commonly exhibit hyperactivity of the salience network during anxiety‐provoking tasks . During external attentional tasks involving nonemotional stimuli, both depressed individuals and nondepressed individuals who ruminate fail to fully deactivate key default network regions . This pattern of hyperactivity is accompanied by increases in resting‐state functional connectivity among key default network regions; reduced connectivity between the medial prefrontal cortex and the nucleus accumbens and amygdala; and biased coupling of frontoparietal control systems with the default network and away from the dorsal attention network .…”
Section: Negatively Biased Self‐generated Thought: Importance Of Statmentioning
confidence: 99%
“…The pars triangularis of the IFG, or more broadly the ventrolateral prefrontal cortex (vlPFC; Ridderinkhof et al, 2004) has a central role in inhibitory control (Swick et al, 2011), specifically in the inhibition of irrelevant or negative information from short-term memory (Berman et al, 2011), and has an important function in memory retrieval (Badre and Wagner, 2007). This brain area is among the most frequently activated regions in connection with rumination (Piguet et al, 2014). These findings are also convergent with the results of Kühn et al (2013), who detected greater left IFG activations among those non-depressed people who tend to experience intrusive thoughts (Kühn et al, 2013).…”
Section: Discussionmentioning
confidence: 99%